Monitoring the lubricant condition in a low-speed rolling element bearing using high frequency stress waves - Jamaludin, N.; Mba, David; Bannister, R. H. (Professional Engineering Publishing, 2002)
This paper presents the results of an investigation into the development of a reliable, nonintrusive and effective technique capable of accessing the lubrication condition within a low-speed rotating bearing. This unique monitoring system is known as pulse injection technique (PIT) and involves transmitting a Dirac pulse through a bearing via a stress waves (SW) sensor. Analysis of measured stress wave signatures differentiated between a properly and poorly lubricated bearing. This method was found to be effective as stress wave propagation is sensitive to the transmission path, which in turn is affected significantly by the type and amount of grease present in the vicinity of the working elements of a bearing. The ability of this technique to monitor the lubrication condition within a bearing whilst in operation could be utilised to determine the appropriate time for grease replenishment or addition.